2003
DOI: 10.1046/j.1439-0426.2003.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of point abundance sampling by electro-fishing modified for short fishes

Abstract: Summary The assessment of fish densities using point abundance sampling by electro‐fishing requires information about the size of the sample area. For electro‐fishing the effective fishing range depends on biological effects such as species and length of fish as well as physical effects like conductivity of water or substrate type. The present study investigates systematically the impact of conductivity and substrate type on the extension of the electrical field of a battery‐powered electro‐fishing gear (DEKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…PAS electrofishing considers the spatial structure of the population or the fish assemblage using numerous small samples instead of one or a few large samples and thus yields a high number of independent samples (Zalewski, ; Persat & Copp, ; Reynolds, ; Scholten, ; Lapointe et al ., 2006 b ). PAS electrofishing was performed according to Persat & Copp () with a duration of 10 s electrical current flow (Scholten, ). The activated ring‐shaped anode without a net (diameter 31 cm), powered by a stationary 8 kW (continuous DC) electrofishing generator (FEG 8000; EFKO GmbH; http://www.efko-gmbh.de), was submerged 20 cm above the bottom for 2 s and then slowly lifted to the surface for the remaining 8 s. Stunned fishes were caught using a round dip‐net (diameter of 48 cm, mesh size 5 mm) by a second person.…”
Section: Methodsmentioning
confidence: 99%
“…PAS electrofishing considers the spatial structure of the population or the fish assemblage using numerous small samples instead of one or a few large samples and thus yields a high number of independent samples (Zalewski, ; Persat & Copp, ; Reynolds, ; Scholten, ; Lapointe et al ., 2006 b ). PAS electrofishing was performed according to Persat & Copp () with a duration of 10 s electrical current flow (Scholten, ). The activated ring‐shaped anode without a net (diameter 31 cm), powered by a stationary 8 kW (continuous DC) electrofishing generator (FEG 8000; EFKO GmbH; http://www.efko-gmbh.de), was submerged 20 cm above the bottom for 2 s and then slowly lifted to the surface for the remaining 8 s. Stunned fishes were caught using a round dip‐net (diameter of 48 cm, mesh size 5 mm) by a second person.…”
Section: Methodsmentioning
confidence: 99%
“…Stunned fishes are less buoyant in cold water, which has lower conductivity (Reynolds 1996); therefore, more time is required for detection when cold, turbid waters are sampled. Scholten (2003) found that differences in conductivity can change the effective fishing range up to 50 cm in large rivers, and that the effective fishing range was highest over sandy substrates and lowest over mud. This can result in an area of attraction that is twice as large in the main channel of a large river compared with the floodplain (Scholten 2003).…”
Section: Discussionmentioning
confidence: 98%
“…The first direct test of sampling duration (the length of time a site is electrofished) for PASE was performed by Scholten (2003) who caged fishes in the vicinity of the anode and determined that sites should be electrofished for 10 s to ensure all fishes are captured. However, his tests were performed in 20 cm of water with low turbidity, a condition rarely met in large rivers.…”
mentioning
confidence: 99%
“…The fish were collected by an electrical aggregate with a continuous choice of electrical parameters (Hans Grassl-ELT62IIHI). The parameters of the electrical current of the aggregate were determined by the water conductivity and were also based on the fish species and their sensitivity to an electrical current, as reported in (Scholten, 2003). The flow depth, the characteristics of the microhabitat, and the velocity were surveyed at the sites where the fish were captured.…”
Section: Ichthyological Survey and Hydrometric Measurementsmentioning
confidence: 99%